Influence of Work-Family Conflict and Work Stress on the Psychological Well-Being among Police Officers in Makurdi Metropolis. - Sunday, Shide; Terzungwe, Anhange Samuel; Okhakhume, S.; Daudu, Daudu Amough (Advances in Social Sciences Research Journal, 2017)
This study investigated the influence of work-family conflict and work stress on the psychological well-being among police Officers in Makurdi metropolis. The study employed a cross-sectional survey design, where three hundred and fourty six (346) police Officers consisting of 202 (58.7%) males and 143 (41.3%) females were used for the study. Their ages ranged from 18 to 64 years with the Mean of 411.61 (SD=11.226). Work- Family Conflict Scale (WFCS), Workplace Stress Scale (WSS) and Ryff’s Psychological Well-being Scale (RPWS) were used for data collection. Statistical analysis involved the use of Multiple regression. Findings from the hypotheses indicated that, work-family conflict significantly influenced psychological well-being among police Officers in Makurdi metropolis. Work stress significantly influenced psychological well-being among police Officers in Makurdi metropolis. Finally, the result showed that, work-family conflict and work stress had significant negative joint influence on psychological well-being among police Officers in Makurdi metropolis. Based on the findings, it was recommended that, Police Officers should be enlightened on how to manage work-family conflict and work stress. On policy basis, it was therefore recommended that government should evolve policies that are aimed at reducing work-family conflict and work stress among police Officers. Also, nongovernmental organizations with caring mind for the police Officers should help reduce work-family conflict and work stress, so as to enhance better policing by the Officers. Finally, more researches should be encouraged on the subject matter for further identification of long term solutions to the problems affecting psychological well-being of police Officers in Makurdi metropolis in particular, and Nigeria at large.